FINANCIAL DETERMINANTS OF INVESTMENT DECISION-MAKING IN FRAUDULENT SCHEMES WITH SCAM AWARENESS AS A MEDIATING VARIABLE AND RISK TOLERANCE AS A MODERATING VARIABLE - Adara Mishel Harjanto; Adi Kurniawan Yusup (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2025)
This study explores how financial literacy, financial behavior, and financial stress influence investment scam awareness, as well as how this awareness shapes investment decisions among Generation Z in Indonesia. This study applies Protection Motivation Theory (PMT) to explain how threat recognition and coping responses explain investors' behavior. Quantitative approach was used for this research with data sourced using an online questionnaire survey distributed to Generation Z investors in Indonesia through purposive sampling method. The data were evaluated using Structural Equation Modeling Partial Least Squares (SEM-PLS) using SmartPLS 4 to test the relationships between variables. The findings indicate that financial literacy has a positive and significant effect on investment scam awareness, allowing individuals to better recognize fraudulent schemes. In contrast, financial behavior and financial stress show no significant effect on awareness of investment scams. Furthermore, scam awareness does not directly affect investment decisions, but risk tolerance was proven to moderate this relationship. These findings show that although financial literacy improves scam awareness, investment decisions are also shaped by other factors. This work offers additional insight to existing literature by delivering a deeper understanding of how financial determinants shape investment decision-making in fraudulent investment contexts, especially among Generation Z investors in Indonesia.